Gastroenteritis associated with accidental contamination of drinking water with partially treated water - FERNANDES, T. M. A. (Cambridge University Press, 2007)
Due to human error, drinking water supplied to a new housing estate in The Netherlands was contaminated with grey water. The cohort of 921 accidentally exposed households (area A) had a higher attack rate for diarrhoea (54·1%) than a non-exposed cohort of 1529 households from an adjacent area (B) (24%) (RR 2·3, 95% CI 1·9–2·7). Household water score showed a dose-response with illness, in both areas A and B. For each 1000 inhabitants, 19·8 cases in area A, 7·0 cases in control area B (RR(AB) 2·2, 95% CI 1·3–3·8) and 3·3 cases in a more distant control area C (RR(AC) 4·6, 95% CI 2·7–8·0) were diagnosed with gastroenteritis by their general practitioner. A gastroenteritis outbreak associated with consumption of contaminated drinking water was observed in the exposed area. The use of grey water was banned in 2003, with the exception of rainwater use for flushing toilets. The risk of rainwater use is currently being investigated.